STUDI PEMANFAATAN LIMBAH BAMBU DAN TEMPURUNG KELAPA DALAM PEMBUATAN BIOBRIKET MENJADI SUMBER ENERGI ALTERNATIF - Saputra, Guntur Hadi; Ilham, Jumiati; Mohamad, Yasin (Program Vokasi-Universitas Negeri Gorontalo, 2024)
The use of fossil fuels has resulted in the emission of greenhouse gases which can trigger global warming. In addition, fossil energy reserves that continue to decrease also raise concerns regarding aspects of their reselience and sustainability. Therefore, new and renewble energy must be developed immediately. The use of biomass as an alternative fuel for Steam Power Plant (PLTU) is in line with Indonesia’s efforts towards net zero emission in the future. In addition to increasing the contribution of renewable energy to the national energy mix, cofiring will also have a positive impact on the development of the circular economy as it can open up employment and business opportunities in the biomass sector, especially those based on garbage and waste. This research aims to determine the value of moisture content, heating value, combustion rate, and electrical energy produced from bamboo twigs and coconut shell waste with different composition variation. The method used in this research is an experimental method in which a bomb calorimeter is used to determine the heating, and a biomass stove is used to determine the combustion rate. The research finding reveals that the best samples for utilizing bamboo and coconut shell waste in the production of bio-briquettes as an alternative energy source are the variety of 200 grams of shell charcoal and 10 grams sago adhesive (sample 9). It is the best sample due to it has moisture content value of 6.38%, heating value of 5663.9 cal/gram, combustion rate is 0.227 gram/minute, and the electrical energy generated by converting the heating value to kWh is 6.5857 kWh/gram. In reference to SNI 01-6235-2000, the moisture content should not be more than 8%, and the minimum heating value is 5000 cal/g.